Revealing the Colonial in Common Sense – Then and Now (KULT_online, 2018)
In Duress: Imperial Durabilities in our Times Ann Stoler offers a collection of essays contributing to the concept-work on the enduring and shapeshifting relations of a colonial past in the political present. With a grand geographical span and a wide topical scope, Stoler’s focus is on how academic and political conceptualizations of colonial history control the parameters with which we understand the world today and how, as a result, imperial structures and relations change. In her analysis, she offers new tools to make “colonial entrails” (p. 4) visible, guided by three main interests: 1) How concepts produce, reflect and maintain inequity 2) The difficulties of writing colonial histories that are entangled in the geo-political present and 3) “Unlearning” about colonial governance and critically engaging with misunderstandings. Duress provides the reader with methodological devices to clarify imperial relations in addition to original historical and political analysis.